(Re)-structuring the CEO’s compensation—the case of Israel - Mroczek-Dąbrowska, Katarzyna; Shemesh, Yaron (Economics and Business Review, 2020)
The executive compensation issue continues to cause protest due to the increasingnumber of cases of an unjustifiably high level of pay. The main conflict arisesfrom the misalignment of interests between the short-term expectations of the managerand long-term needs of the shareholders. Since there are no universal rules on how toprice the executive performance companies reach for different means of establishingthe CEO’s compensation and ascertaining manager’s commitment towards maintaininga company’s value. The issue becomes more complex once the compensation rules arenot a direct effect of the market power game but are additionally restricted by government.The aim of the paper is to discuss corporate government policies introduced inIsrael and their impact on executive compensation level and structure. Israel is amongstthose countries that partially regulate CEO compensation and thus the Israeli experiencecan add to the understanding of the effectiveness of modern corporate governance.